THE SENSE OF SELF EFFICACY OF PRE-SERVICE ENGLISH TEACHERS IN EFL CONTEXT - Devina Eka Safitri (SAGA: Journal of English Language Teaching and Applied Linguistics, 2021)
This study aims to describe the sense of self-efficacy of pre-service teachers in the context of EFL. This issue needs to be discussed because of the importance of self-efficacy in teaching for the pre-service teacher. The study used the Teacher Sense of Efficacy Scale (TSES) questionnaire as the instrument. There were 103 respondents participated in this study. The results showed that pre-service English teachers were more effective on instructional strategy with an average score of 3.7840 of the overall sense of efficacy. Then, followed by student engagement efficacy with an average score of 3.7561, and the last one is class management with an average score of 3.7318. Based on the data obtained, it shows that the students' sense of efficacy is at a moderate level.